From Hayal ve Hakikat to Enin: the literary life of Fatma Aliye - Akdemir, Fatma. (My University, 2015)
This thesis aims to discuss the literary life of Fatma Aliye by focusing on her novels Hayal ve Hakikat, Refet, Udi, Levayih-i Hayat and Enin. The starting point of this work is the relationship between Fatma Aliye’s first novel Hayal ve Hakikat, which she wrote together with Ahmet Midhat and is often neglected in studies on Fatma Aliye, and her last novel Enin. Hayal ve Hakikat and Enin resemble each other in many aspects, such as the narratives of the individual lives of their female protagonists and plotlines. However, while in Hayal ve Hakikat the female writer and protagonist are placed in a secondary position against the backdrop of patriarchal authority, in Enin the gender norms are reversed and woman's authority comes to the foreground. In order to understand the contrast between Fatma Aliye’s first and last novels, this study chronologically evaluates her other novels and tries to depict the main changes in Fatma Aliye’s literary style.